131 Pooled safety data from the risdiplam clinical trial development programme. Issue 6 (27th May 2022) - Servais, Laurent; Baranello, Giovanni; Chiriboga, Claudia; Darras, Basil; Bader-Weder, Silvia; Gorni, Ksenija; Jaber, Birgit; McIver, Tammy; Scalco, Renata; ,
Abstract : Risdiplam is a centrally and peripherally distributed oral survival of motor neuron 2 (SMN2) pre mRNA splicing modifier that increases the levels of functional SMN protein. Risdiplam (EVRYSDI™) has been approved by the US Food and Drug Administration for the treatment of patients with spinal muscular atrophy (SMA), aged 2 months and older. The risdiplam clinical development programme consists of four studies in a broad population of individuals with SMA. FIREFISH (NCT02913482 ) and SUNFISH (NCT02908685 ) are two-part studies assessing safety, tolerability, pharmacokinetics (PK), pharmacodynamics (PD) and efficacy in infants with Type 1 SMA and patients with Type 2/3 SMA, respectively. JEWELFISH (NCT0302172) assesses safety, tolerability, PK and PD in patients with SMA who previously received RG7800 (R06885247), nusinersen (SPINRAZA®), olesoxime or onasemno- gene abeparvovec-xioi (ZOLGENSMA®). RAINBOWFISH (NCT03779334 ) assesses efficacy, safety, PK and PD in infants with genetically diagnosed and presymptomatic SMA. Pooled analyses of FIREFISH and SUNFISH Parts 1 and 2 and JEWELFISH were conducted to determine the long-term safety profile of risdiplam. At the data-cut (15th January 2020) no treatment-related safety findings led to withdrawal from up to 39 months' risdiplam treatment in 465 patients. Here we will present updated pooled safety analyses for the risdiplam studies. g.baranello@ucl.ac.uk